Novel star HPMA-based polymer conjugates for passive targeting to solid tumors - Etrych, T; Strohalm, J; Chytil, P; Říhová, B; Ulbrich, K (Journal of drug targeting, 2011)
Novel star polymer-doxorubicin conjugates designed for passive tumor targeting have been developed and their potential for treatment of cancer has been investigated. In the present study the synthesis, physico-chemical characterization, drug release, bio-distribution and preliminary data of in vivo efficacy of the conjugates are described. In the water-soluble conjugates the core of a molecule formed by poly(amido amine) (PAMAM) dendrimers was grafted with semitelechelic N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers bearing doxorubicin (Dox) attached by hydrazone bonds enabling intracellular pH-controlled hydrolytic drug release, or by GFLG sequence susceptible to enzymatic degradation. The controlled synthesis utilizing semitelechelic copolymer precursors facilitated preparation of polymer conjugates in a broad range of molecular weights (1.1-3.0·10(5) g/mol). In contrast to free drug or linear conjugates the star polymer-Dox conjugates exhibited prolonged blood circulation and enhanced tumor accumulation in tumor-bearing mice indicating important role of the EPR effect. The star polymer-Dox conjugates showed significantly higher anti-tumor activity in vivo than Dox?HCl or its linear or graft polymer conjugates, if treated with a single dose 15 or 5 mg Dox eq./kg. Method of tumor initialization (acute or chronic experimental tumor models) significantly influenced effectiveness of the treatment with much lower success in treatment of mice bearing chronic tumors.
Keywords: nosiče léků; Drug Carriers; Delayed-Action Preparations; Tissue Distribution; Doxorubicin; akrylamidy; Lymphoma, T-Cell; voda; koncentrace vodíkových iontů; myši inbrední C57BL; mužské pohlaví; Mice; lékové transportní systémy; Water; Dendrimers; Acrylamides; dendrimery; léky s prodlouženým účinkem; doxorubicin; ženské pohlaví; zvířata; tkáňová distribuce; Hydrogen-Ion Concentration; Antibiotics, Antineoplastic; myši; lymfom T-buněčný; Solubility; protinádorová antibiotika; Drug Delivery Systems; Female; rozpustnost; Mice, Inbred C57BL; Male; Animals